The Russian Second Generation in Tallinn and Kohtla-Järve The TIES Study in Estonia - Vetik, Raivo; Helemäe, Jelena (IMISCOE Reports, 2011)
This important study analyzes the challenges faced by second-generation Russians in post-Soviet Estonia, and, in doing so, explores the interrelationships between ethnicity and social equality. It will be of great value to scholars of immigration, cultural assimilation, ethnicity, and nationalism.